PENGARUH CITRA PERUSAHAAN TERHADAP WOM DAN LOYALITAS NASABAH (STUDI PADA NASABAH BANK BPD. BALI DI DENPASAR) - I Putu Danika Angga Putra; Ni Nyoman Kerti Yasa; I Putu Gde Sukaatmadja (Forum Manajemen STIMI Handayani Denpasar, 2015)
The purpose of this study was to determine the influence of corporateimage on WOM dan customer loyality. The population in this study were allcustomer of Bank BPD Bali at Denpasar city. Sampling method used is purposivesampling, in order to obtain as many as 130 respondents. Analysis technique usedis Structural Equation Model (SEM). The results showed that the corporate imagehave a significant positive effect on WOM, dan corporate image have positive dansignificant effect on the intention to customer loyalty dan WOM have significant effecton customer loyalty. With this study, expected to be useful for the party leadership S2FE program Unud in enhancing the corporate image of the Bank BPD Bali, positiveWOM Bank BPD Bali, dan customer loyalty.